Flotation and concentration of the mineral manganese MnO2 - Azañero O., Ángel (2006)
The ores of manganese are difficult to concentrate, nevertheless in this study of research, it has been achieved to raise the grade of manganese applying different equipments, machines, flow charts and diverse chemical reagents of flotation, obtaining the best results by means of flotation of the gangue, being the tail the concentrate of manganeso. The original ore has 23,8% Mn, on having it concentrate by inverse flotation, one manages to obtain 47,50% Mn in the concentrate, product very quoted on the intermal and external market.